Experimental study on diesel's twin injection and spray impingement characteristics under marine engine's conditions. (15th October 2021) - Xia, Jin; Zhang, Qiankun; He, Zhuoyao; Wang, Jianping; Liu, Rui; Qian, Yong; Ju, Dehao; Lu, Xingcai
Highlights: Diesel's twin injection and impingement characteristics are investigated. Twin-spray impingement forms a spray fan and larger spatial distribution. The collision R-parameter range is smaller than that of the single free spray. The twin injection reduces the requirement for ultra-high injection pressure. Abstract: In the large-bore marine engine, two and more injectors are mounted on each cylinder to achieve the dual-fuel combustion mode and promote the fuel-gas mixing performance, although the spray impingement is inevitable. Motivated by the applications of impinging jets on rocket engines and aero-engines, twin injectors were configured based on a large-scale constant volume chamber. The diesel's twin injection and symmetrical impingement process were captured using different optical techniques. A total of 72 experimental cases were conducted under sub/trans/supercritical conditions with various injection pressures from 60 MPa to 180 MPa. Results show that different critical conditions dominate the spray's impingement characteristics. As the twin-spray penetrates and collides, the droplets tend to coalesce, bounce, separate, and then form a spray fan. The supercritical condition reduces the influence of ambient pressure on the post-collision development at the 180 MPa injection pressure. Higher injection pressure also has a limited effect to further enhance the spatial distribution and phase transition process under the supercritical pressure condition. Compared with the single free spray, the twin-spray impingement shows a shorter duration of fuel-gas mixing and reduces the requirement for ultra-high injection pressure. Moreover, the twin-spray impingement forms a higher radial diffusion rate to enhance the interaction with the ambient gas, although its collision R-parameter range is smaller than that of the single free spray. In general, this work attempts to explore the outcomes of spray impingement during the twin injection process. The results guide the future work of injection strategy optimization and combustion mode conversion for marine engines.